Management of Islamic Education in the Family to Grow Children's Personality - Mudzakir, Mudzakir; Sucahya, Media; Sutarman, Adang (Journal of Asian Islamic Educational Management (JAIEM), 2023)
This article aims to analyze the management of Islamic education in the family to grow children's personalities. Library research was used as a method in this study, starting from collecting data by reading and studying books, scientific articles, magazines, newspapers, and other references related to the study. The results of the study reveal that the position of the family in managing Islamic education for children is the basic determinant, because children are born in a state of purity. Starting from the management of Islamic education in the family environment, the child's personality grows and develops. Management of Islamic education carried out by parents through the process of learning, coaching, training, instilling religious values, parenting, and responsibility is directed to a good and noble habit gradually and continuously. Good management of Islamic education is able to form good children's personalities by emphasizing the aspects of faith, worship, and morals which are implemented in the form of exemplary by parents.